The fast globalizing gendered construction of teacher education: A critical feminist research policy analysis of the contemporary reform movement - Mooney Simmie, Geraldine (Frontiers in Education, 2023)
Gendered narratives of teacher education often rely on research studies that examine the living contradictions of practice in a fast globalizing educational reform ensemble. Here, I argue that it is equally important for women in the academy of teacher education to conduct critical feminist research into the gendered construction of teacher education in macro policy landscapes to reveal, challenge, and change the new hegemonic masculinities at play in higher education in contemporary times. In this study, I conduct a critical feminist scrutiny of this macro policy problem, structures, strictures, and cultural symbols that increasingly contain the gendered construction of teacher education in an ecosystem in higher education imbued with patriarchy and elite conservativism. I selected for scrutiny two recent OECD policy texts, concerned with the problem of inclusion and the framing of gendered relations. A critical feminist discourse analysis of the policy documents in relation to the problem of gender justice shows that the gendered construction of teacher education in this fast globalizing reform ensemble fails to trouble a new consciousness for egalitarian gender relations. The study found that constraints and failures can be explained, if not fully, by the privileging of new hegemonic masculinities in the framing of teacher education at the macro policy level. My argument is centered on a reflexive view of teacher education as an academic and ethical study of human development and change that needs to foreground egalitarian gender relations for emancipatory practices that can offer hope and solidarity in transformative ways that can inspire deep learning and deep democracy.